KEPUTUSAN PEMBELIAN DITINJAU DARI CITA RASA, KEMASAN DAN INOVASI PRODUK PADA AYAM GEPREK MILLENIAL DI COLOMADU - Astin Maharani; Istiqomah Istiqomah; Raisa Aribatul Hamidah (ITB AAS Indonesia Surakarta, 2023)
This research was conducted to determine the effect of taste, packaging and product innovation on purchasing decisions for Millennial Geprek Chicken in Colomadu. This research is a quantitative study and uses data analysis techniques, namely the classical assumption test (normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis, model feasibility test (F test), t test, and the coefficient of determination (R2). The population in this study were all customers who visited millennial geprek chicken at least 2 times with the aim of buying products sold at millennial geprek chicken in Colomadu. The number of population in this study is not known with certainty. The sampling technique in this study used purposive sampling of 100 respondents. Based on the results of hypothesis testing, especially the F test, it is known that Taste, Packaging and Product Innovation simultaneously have a positive and significant effect on purchasing decisions. The results of the t test show that Taste, Packaging and Product Innovation have a positive and significant effect on purchasing decisions. Keywords: Purchase Decision, Taste, Packaging and Product Innovation